Pancreatitis in multiple acyl CoA dehydrogenase deficiency: An underdiagnosed complication. Issue 1 (19th October 2020) - Elkhateeb, Nour; Chakrapani, Anupam; Davison, James; Grunewald, Stephanie; Batzios, Spyros
Abstract: Background: Multiple acyl‐CoA dehydrogenase (MADD) deficiency represents a rare fatty acid oxidation disorder where sporadic reports of pancreatitis already exist. Here, we report three cases of MADD with pancreatic involvement raising questions whether this represents an incidental finding or it is related to the pathophysiology of MADD. Methods: We have retrospectively studied the clinical, biochemical and radiologic data of patients with MADD diagnosed in our department over the last 20 years to identify patients with pancreatic involvement. RESULTS: Three out of 17 patients had pancreatic involvement. All three patients were diagnosed with MADD in the neonatal period (two‐third symptomatic—riboflavin nonresponsive, one‐third asymptomatic via newborn screening—riboflavin responsive). Age at presentation of pancreatitis ranged from 20 months to 11 years. Presentations included a single episode of acute pancreatitis in the first patient, chronic necrotizing pancreatitis in the second patient, while the third patient was diagnosed with chronic pancreatitis (CP) incidentally through ultrasonography. All patients had inflammation features on either abdominal computed tomography or ultrasound. Pancreatic enzymes were elevated in two patients. Management of pancreatitis was done conservatively while the patient with necrotic CP required subtotal pancreatectomy. DISCUSSION: Our data suggest that pancreatitis might be more common in patients with MADD than previously reported, requiring a high index of suspicion in patients with acute metabolic decompensation or nonspecific abdominal symptoms. We hypothesize that the underlying mechanism of pancreatitis in MADD is similar to that in mitochondrial disorders, both resulting from disordered energy metabolism and oxidative phosphorylation.